A study on the physico-chemical changes occurring in ghee (butter oil) during storage - Gosewade, Saurabh; Gandhi, Kamal; Ranvir, Suvartan; Kumar, Anil; Lal, Darshan (Indian Journal of Dairy Science, 2017)
The effect of storage on physico-chemical changes in ghee in relation to oxidation with and without the addition of antioxidant (BHA at 0.02%) was studied. There was a small increase in Reichert Meissl (RM) value, Polenske value and saponification value, and there was a small decrease in iodine value, Butyro- refractometer (BR) reading at 40ÂºC, residual BHA content. Small increase in Peroxide value, Conjugated diene and free fatty acid content (% oleic acid) in ghee during storage at 37ÂºC was also seen and this increase was comparatively less in ghee samples added with antioxidant (BHA) than control ghee samples.